(untitled) (European Journal of Education and Psychology, 2010)
The main purpose of this research has been to analyze the prevalence of specific learning disabilities (LD) in Spanish adolescents. A first study was conducted in the Canary Islands region to analyze the prevalence of individuals identified as LD in the Canary Islands region. A second study was designed to test whether the identification of LD students should not be only based on curricular criteria but also on standardized specific criteria in each academic subject (i.e., reading, writing, arithmetic, etc.). We found that the greater proportion of individuals with special educational needs is identified as LD. This fact is a consequence of the lack of specific criteria to identify students within this category in the Special Education field. Likewise, when psychometric criteria for LD identification are used, the percentage of students identified as LD is lower dramatically.